Влијанието на интерните цени врз успешноста на центрите на одговорност во мултинационалните претпријатија - Скрческа, Анита (Економски факултет, УКИМ, Скопје, 2017)
Multinational enterprises, regardless of size, are facing the issue of transfer pricing between related enterprises, also considered responsibility centers. Since multinational enterprises operate in several countries with different environment, the overall performance of responsibility centers will impact the performance of multinational enterprises, and the applied transfer pricing method, in turn, impact on the performance of the responsibility centers. The analysis of the impact of transfer pricing on the performance of responsibility centers is of particular importance for the management of multinational enterprises, in order to properly measure and evaluate the results of responsibility centers, to achieve goal congruence and to achieve optimal results within the multinational group. In order to study the main subject of research and to accomplish the assigned tasks, the present doctoral dissertation analyzes the advantages and disadvantages of transfer pricing methods and their application in different settings. As a result, the paper outlines a set of guidelines that stand for the boundaries of the defined framework for determining an optimal transfer price. This should help balance the overall goal congruence with an effective independence of each responsibility center, thus ensuring maximum profit for the multinational enterprise as a whole. In order to achieve the main goal, determine and analyze the impact of transfer pricing on the performance of responsibility centers in multinational enterprises, this study includes a survey in several multinational enterprises in the Republic of Macedonia, with authorities’ interpretations on the applied practices for transfer pricing. Outcomes and conclusions presented in this doctoral dissertation are based on theoretical and empirical research. Empirical data were obtained through the survey method. Based on the processed data and obtained results, it can be concluded that internal transfers between related entities are significant. Furthermore, transfer pricing has a considerable impact on the performance of responsibility centers in multinational enterprises. The obtained data indicate that the policy for transfer pricing is centrallized and strategically implemented.
Impact of transfer pricing on the performance of responsibility centers in multinational enterprises
Докторска дисертација одбранета во 2017 година на Економскиот факултет во Скопје, под менторство на проф. д–р Блажо Недев.
Keywords: multinational enterprises, responsibility accounting, responsibility centers, transfer pricing, performance of responsibility centers